Não há você sem mim: histórias de mulheres sobreviventes de uma tentativa de homicídio - Azevedo, Ana Karina Silva (2013)
The murder-suicide (H / S) has been defined as a shocking crime in which a person takes the life of another and then kills himself within 24 hours. Set up as a gender violence, because men are in majority, the killers and the women victims. This study aims to understand the meanings of the experience of a H / S, from women who have survived this act. This study sets up as a hermeneutic phenomenological research, based on Heidegger`s ontology. We interviewed three survivors of H / S, whose narratives allowed to approach the senses present in their lives. The interviews were transcribed and interpreted in accordance with the hermeneutic circle, as proposed by Martin Heidegger. From the interviews of research participants perceive that these women have built their senses in stocks, represented the family foundation and the presence of a husband and children. This project that moved their lives toward the construction of modes-of-being. We noticed the presence of historicity constructing meanings for the existence of these women. We found reports of an experience of loving relationships characterized by strong jealousy, with the presence of fantasies of betrayal, and marked by a careful affective relationship that put them in the position of object possession of his companions. Reflect that such caring restricted their existence being-for-husband. So the senses that moved their stocks, which aimed his ways existential, was the creation of a family, a reference to their lives, to live a love, and care for the children. Therefore, beyond the already known aspects in studies on violence against women, which made these women continue to choose this relationship was the sense that they had for their existence. It is hoped that this study will contribute to the construction of a new look on violence against women, taking as a basis the Heideggerian hermeneutic phenomenology